Проблемні питання кримінальної відповідальності за ст. 130 Кримінального кодексу України - Старко, О.; Starko, О. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статтю присвячено проблемі кримінальної відповідальності за зараження вірусом імунодефіциту людини чи іншої невиліковної інфекційної хвороби. Досліджується питання щодо невдалого визначення законодавцем збудників інфекційних хвороб у назві та диспозиції статті, обґрунтовується положення про те, що злочин, передбачений ч. 1 та ч. 2 ст. 130 Кримінального кодексу України може бути вчинено не лише шляхом дії, а й бездіяльності. Розглядається дискусійне питання щодо моменту закінчення злочину у формі зараження, виявлено недоліки щодо визначення суб’єкта злочину. Сформульовано пропозиції щодо удосконалення законодавства та практики застосування. The article is devoted to the problem of criminal responsibility for the infecting others with human immunodeficiency virus and other incurable infectious diseases. The author argues the issue of inappropriate use in the dispositions of the Code article wording, which implies exclusively viral origin of infectious diseases. The emphasis is laid on the content characteristics of the «incurable infectious diseases». The article considers the matters concerning the forms of infecting, substantiates the conclusion that endangering infection and infecting can be committed either by action or inaction or negligence. The study sheds light on the debatable issue of crime completion moment, as well as the issue of the subject of a crime. The author suggests ways to improve the criminal law and its practical application with a view to greater efficiency of criminal justice response in the field of combatingcriminal proliferation of human immunodeficiency virus and other infectious diseases.
Problematic Issues of Criminal Liabilityunder Art. 130 of the Criminal Code of Ukraine
Keywords: кримінальна відповідальність; зараження; поставлення у небезпеку зараження; ВІЛ-інфекція; невиліковна інфекційна хвороба; суб’єкт злочину; criminal liability; infection set out in the risk of infection; the HIV- infection; incurable infectious disease; the subject of crime